2020
DOI: 10.1097/ico.0000000000002549
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Novel Confocal Microscopy Imaging Protocol With Assessment of Reproducibility and Comparison of Nerve Metrics in Dry Eye Disease Compared With Controls

Abstract: The purposes of this study were to assess the reproducibility of a novel standardized technique for capturing corneal subbasal nerve plexus images with in vivo corneal confocal microscopy and to compare nerve metrics captured with this method in participants with dry eye and control participants.Methods: Cases and controls were recruited based on their International Statistical Classification of Diseases and Related Health Problems (ICD-10) diagnoses. Participants completed the following 3 ocular symptom quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 46 publications
1
14
1
Order By: Relevance
“…14 While another study by Misra et al 12 reported higher intrareliability for fiber length using wider inferior whorl montages and manual nerve tracing, interobserver repeatability was lower potentially due to the difference in experience levels between observers involved in the study. Lower reliability in inferior whorl measurements including length and fractal dimension was also reflected in a recent study by Takhar et al 21 in comparison with a standardized fuller montaging procedure which included the central cornea. However, their image selection criteria were not fully specified and image quality or artifacts may have affected on the corneal nerve measurements as evidenced by the low nerve fiber length mean value of their full montage analysis in healthy controls (CNFL: 10.15 mm/mm 2 ) as compared with typical values reported by the current study and most researchers using ACCMetrics analysis (usually ranging from about 14-19 mm/mm 2 ).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…14 While another study by Misra et al 12 reported higher intrareliability for fiber length using wider inferior whorl montages and manual nerve tracing, interobserver repeatability was lower potentially due to the difference in experience levels between observers involved in the study. Lower reliability in inferior whorl measurements including length and fractal dimension was also reflected in a recent study by Takhar et al 21 in comparison with a standardized fuller montaging procedure which included the central cornea. However, their image selection criteria were not fully specified and image quality or artifacts may have affected on the corneal nerve measurements as evidenced by the low nerve fiber length mean value of their full montage analysis in healthy controls (CNFL: 10.15 mm/mm 2 ) as compared with typical values reported by the current study and most researchers using ACCMetrics analysis (usually ranging from about 14-19 mm/mm 2 ).…”
Section: Discussionmentioning
confidence: 84%
“…The images were analyzed with the fully automated analysis software ACCMetrics (The University of Manchester Intellectual Property UMIP, Manchester, United Kingdom) to measure corneal nerve parameters. [19][20][21][22] To compare the reproducibility of parameters between the central cornea and inferior whorl region, central CNFL and corneal nerve fractal dimension (CNFrD), and inferior whorl length (IWL) and inferior whorl fractal dimension (IWFrD) were prioritized parameters in this study. This process was conducted on 2 occasions: timepoint 1 and timepoint 2, 1 week apart with rerandomization of the same image folders to assess for intraobserver reliability for each of the 3 observers.…”
Section: Image Selection and Reproducibilitymentioning
confidence: 99%
“…A sterile, single-use disposable cap (TomoCap) was used for each subject, after applying GenTeal Gel (hypromellose 0.3%) into the cap as a coupling agent. The subbasal nerve plexus was imaged using a method validated by Takhar et al [20]. A 5 × 5 dot grid system was placed in front of the fellow eye of the subject.…”
Section: Study Proceduresmentioning
confidence: 99%
“…These metrics include corneal nerve fibre length (CNFL), corneal nerve fibre density (CNFD), and corneal nerve branch density (CNBD). CNFL is regarded as the primary biomarker showing an early reduction in diabetes [ 77 ], and it is also the most reproducible corneal nerve metric [ 78 ]. Together with CNFD and CNBD, they make up three key CCM parameters, that enable an assessment of nerve degeneration and regeneration ( Table 2 ) [ 79 ].…”
Section: Ccm Image Acquisition and Analysismentioning
confidence: 99%
“…The narrow field of view of individual images has been perceived as a limitation, as such, some centres have used wide field imaging to create sub-basal nerve plexus maps [ 85 ]. Participants are asked to focus on a number of dots across a square grid in a systematic process, with images acquired mapping out the corneal sub-basal nerve plexus and inferior whorl [ 78 ]. Whilst manual annotation has demonstrated reliability and reproducibility [ 30 , 86 ], it is labour intensive and requires considerable expertise [ 81 , 84 ].…”
Section: Ccm Image Acquisition and Analysismentioning
confidence: 99%